EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V DI SDN 02 BENGKAYANG - Lamria Sitompul; Totok Victor Didik Saputro (STKIP Subang, 2026)
ABSTRACT This study aims to analyze the effectiveness of the Think Pair Share (TPS) cooperative learning model on the mathematical problem-solving ability of fifth-grade students at SDN 02 Bengkayang on the topic of the perimeter of flat shapes. This study employed a quantitative approach with a quasi-experimental nonequivalent control group pretest-posttest design. The sample consisted of 42 students, namely class VB as the experimental group and class VC as the control group, each comprising 21 students. Data were collected through essay-based story problem tests and observation sheets. The instruments were validated using Aiken's V (V = 0.813) and tested for reliability using the Percentage of Agreement Borich method (PA = 98.25%). Data analysis was conducted using the Shapiro-Wilk test, Levene test, and Independent Sample t-test with SPSS. The results showed that the average posttest score of the experimental class (72.19) was higher than the control class (57.38), with the experimental class improvement (38.76 points) being almost twice as large as the control class (19.67 points). The Independent Sample t-test yielded a significance value of 0.035 (sig. < 0.05), leading to the rejection of H₀ and the acceptance of H₁. Observation results indicated that the experimental class achieved a completion rate of 96.3% (very good) and the control class 81.5% (good). It is concluded that the TPS model is effective in improving the mathematical problem-solving ability of fifth-grade students at SDN 02 Bengkayang.